Morphometric Analyses of (Hidden) Directional Asymmetry in Leaf Blades - Baranov, Sergey Gennadevich (Ital Publication, 2018)
The deviation from perfect bilateral symmetry is a phenomenon actively exploring in evolutionary and environmental studies. The bilateral variation presents on different ecosystem level. The methods applied vary depending on the task and the final goal of study. The present study demonstrates the statistically significant presence of components (traces) of directional asymmetry (DA), fluctuating asymmetry (FA) and antisymmetry (AS) in leaf blade of Betula pendula on low level of ecosystem such as tree and leaf blade. The Generalized Procrustes Analysis was applied for testing asymmetry of shape in all data set and subgroups. The category ‘population’ revealed no significant value of DA (factor ‘side’). In the levels ‘tree’ and ‘leaf blade’ the factor ‘side’ was statistically significant as well as fluctuating asymmetry (factor interaction ‘leaf × side’).The principal component analysis showed visually the difference in PC scores between antisymmetry matrices of the left and right halves of the leaf blade. Covariate analysis matrices demonstrated the shape deviation from strict symmetry. The metric traits showed directional asymmetry in t-test in the leaf blade and the low kurtosis values. Permutation test of kurtosis values in geometric morphometric approach showed deviation from normality that could verified as a weak presence AS traces. The discriminant analysis results showed that traces of DA differed at the subpopulation level, as three of 10 populations revealed not significant factor ‘side’. Descriptive statistics of the metric train showed a correspondence to the trace of directional asymmetry in the shape of leaf blade. Fluctuating asymmetry in its pure form, at three levels of ecosystem was met only in single population of ten that should be taken into account testing developmental stability of birch and possibly other woody plants.